About a woman [compact disc] - Rhett, Thomas, 1990- (The Valory Music Co., 2024)
One of the most engaging and consistent country chart-toppers of the last ten years, Thomas Rhett has emerged as a superstar with as much songwriting prowess as stadium-rocking charisma. Marking the start of a fresh creative chapter, his upcoming seventh studio album is full of heart-pounding country with a progressive edge, high-energy anthems and quick-hitting lyrics amid lush soundscape, proving why Thomas Rhett once again leads the evolving genre without forgetting its roots.